MAPPING OF CORAL REEF ECOSYSTEM IN THE NATUNA ISLANDS USING ALOS IMAGERY - Suyarso .; Yaya Ihya Ulumuddin; Bayu Prayuda (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The coral reef ecology of the Natuna Islands has been studied over 10 years. However, none of those studies produced a coral reef map. Maps of coral reef ecosystem are important for planning, management and monitoring tool. The present study integrates the 115 field data and the ALOS satellite data, using depth invariant index algorithm to generate coral reef ecosystem classes. Those classes are: life corals, dead coral and rubble aggregates, mixing of substrates and sand. The algorithm that composed of three visible bands is applicable at clear water rather than at turbid water environment. Hence, vegetation coverage as well as seagrass, seaweed and macro algae which are in small extent and usually covered by fine sand materials and associated with turbid water, cannot be classified.The aim of this research, which is funded by Critic Coremap – LIPI, is to produce map of coral reef ecosystem in the Natuna Islands.